VIRTUAL SCREENING OF HETEROCYCLIC COMPOUNDS AGAINST ANGIOTENSIN-CONVERTING ENZYME FOR POTENTIAL ANTIHYPERTENSIVE INHIBITORS - LOBO C, ZOZIMUS DIVYA; MOHAMED A, SYED; SHANMUGAM, GNANENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to investigate the antihypertensive activity of heterocyclic compounds against angiotensin-converting enzyme (ACE) through molecular docking studies. Methods: The X-ray crystal three-dimensional (3D) structure of human ACE complexed with lisinopril (PDB ID: 1O86) was retrieved from protein databank. The two-dimensional structures of 10 selected heterocyclic compounds were drawn in ACD-Chemsketch and converted into 3D structures. The 3D structures of compounds were virtually screened in the binding pockets of ACE using FlexX docking program. Further, the chemical entities revealing the molecular electronic structures of the best docked compound (Compound-4) were explored through density functional theory studies. Results: The Compound-4 showed the highest docking score of −26.6290 kJ/mol with ACE. The Hbond and non-bonded interactions are favored by phenylalanine, leucine, and arginine. The energy gap of 1.60 eV between highest occupied molecular orbital and lowest unoccupied molecular orbitals explained the presence of strong electron-acceptor group. Furthermore, the molecular electrostatic potential studies clearly envisaged the requirement of electropositive and electronegative groups are crucial for the ACE inhibitor activities. Conclusion: The identification of good ACE inhibitors requires the understanding of the current ACE inhibitors. Thus, the docking interactions of Compound-4 and its molecular electronic structure significantly imply its potential as antihypertensive agent. However, further clinical studies are required to ascertain its potential toxic effects.